ESTIMATING AND ANALYSING OF DEMAND FUNCTION FOR POULTRY IN IRAQ ROR THE PERIOD (1990 - 2009) - Salim Al-Youzbaki; Suha Mohammad Ahmad Al_Hmdany (Mesopotamia Journal of Agriculture)
The study aimed assessment and analysis of the demand function for poultry meat in Iraq for a period (1990-2009) once without changing time and again with the time factor as well as find food gap and the values ​​of elasticities (price and Aldkhalah and Cross) and predict the required quantities of this meat in the coming years. It was found that the variables (the average per capita income and the size of the population and the prices of poultry meat, red meat, and time) has been deleted variable V average prices of fish meat from the equation for not Manueth. Has appeared significant in influencing and varying in the degree of impact, it turns out that the coefficient of determination of the model with time has reached (97.9%), while the coefficient of determination with no time (97%) This indicates that analysis with time has increased from clarification impact on payment of poultry meat, and the results show the growing size of the food gap and rate 28.18 thousand tons of poultry meat in the period studied, also reached values ​​elasticities without and with time and sequentially price (-0.167, -0.123) and Aldkhalah (0.017, 0.032) and cross of red meat (0.192, .240) and cross the fish meat with time (-0.221) value price elasticity of demand 0.510, indicating that demand for poultry meat is flexible towards change in price, while the flexibility of domestic demand 0.017, indicating that the required quantity of the commodity changed much less than the change in income.